Teaching English in Eastern Part of Indonesia: Challenges and Opportunities - Nakul, Devi Syahfira; Murtafi'ah, Banatul (FKIP - Universitas Tanjungpura, 2024)
Though several researchs regarding teaching English in rural areas has massively been conducted, most of them focused on the challenges and none to few of them discussed the opportunities. This research, therefore, aims to look at the challenges and opportunities of the teaching experience of a pre-service English teacher when participating in the Kampus Mengajar program in the eastern part of Indonesia. The research method used is a qualitative study that specifically employed phenomenology as the design. Furthermore, this research was conducted in Serui City, Papua with data collected in the form of video and audio recordings from teaching grade 4 and 5 students of elementary school as well as the interviews with the principal of the school. The results of this study showed four challenges including: the absence of English teachers; lack of English competence (vocabulary, spelling, pronunciation); students